Eksplorasi Etnomatematika pada Proses Pembuatan Jajanan Tradisional Kue Putu di Poncokusumo Kabupaten Malang - Indanaa Zulfaa; Annafi Awantagusnik (FKIP Universitas Mataram, 2026)
To address the problem of abstract mathematics learning, a learning approach is needed that connects mathematical concepts to students' real-life contexts. One approach that could provide a solution is ethnomathematics. This study aims to explore the ethnomathematics concept found in the process of making traditional Putu cake and analyze its potential as a mathematics learning medium in Junior High Schools. This study uses a descriptive qualitative method with an ethnographic approach. Data collection was conducted through observation, semi-structured interview with two Putu cake makers and sellers, and documentation at the production site in Sukosari, Pandansari, Poncokusumo, Malang Regency. Data analysis was carried out qualitatively through three stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that each stage of Putu cake making contains mathematical concepts. In the stages of preparing ingredients and making dough, the concepts of spherical geometry, number operations, and comparisons were found through adjusting the measurements of ingredients based on the production quantity. The stages of forming and filling the dough into the mold contain the concepts of cylindrical geometry and hollow cylinder geometry as shown by the uniformity of the size of the bamboo mold. In the steaming stage, the concept of ratio and comparison between mold size and steaming time was found, while in the presentation and packaging stage, the concept of cylindrical geometry reappeared in the final form of Putu cake. Based on these findings, Putu cake has strong potential to be developed as a contextual and local culture-based mathematics learning medium in junior high schools for the material of numbers, ratios, and geometry. Using Putu cake as a learning medium allows students to understand mathematical concepts through real-life experiences while fostering an appreciation for local culture. Further research is recommended to test the effectiveness of using Putu cake as a medium for learning mathematics in the classroom.